Evaluating lignin valorization via pyrolysis and vapor-phase hydrodeoxygenation for production of aromatics and alkenes. Issue 8 (2nd April 2020) - Saraeian, Alireza; Aui, Alvina; Gao, Yu; Wright, Mark M.; Foston, Marcus; Shanks, Brent H.
Abstract : Lignin valorization to chemicals is an important component of creating economically viable biofuels production from lignocellulosic biomass. Abstract : Lignin valorization to chemicals is an important component of creating economically viable biofuels production from lignocellulosic biomass. Any such strategy should aim at producing chemicals used at scales that can appropriately match lignin availability. Herein, a combined pyrolysis and low-pressure hydrodeoxygenation (HDO) process configuration is proposed to achieve total oxygen removal and obtain hydrocarbon (aromatic and alkene) products. This approach is tested for its robustness for lignin feedstocks obtained from a variety of sources and extracted using different procedures. The experimental results demonstrate that regardless of the lignin source, the HDO process using a MoO3 catalyst was able to funnel the complex mixture of pyrolysis vapors to mono-aromatics (17–29 C%), as well as alkenes and alkanes. The formation of char from lignin pyrolysis retains more than 50% of the feed carbon in the pyrolyzer, allowing only a portion of carbon to volatilize and be converted to products. A partial depolymerization technique is employed on one of the lignin samples prior to pyrolysis as an example of how the amount of char can be drastically reduced leading to an increased yield of aromatics (53–55 C%). Techno-economic analysis based on the experimental results suggest significant economic benefit of this strategy compared to using lignin as simply a boiler feed.